Current status of outcome measure development in vasculitis. - Merkel, P; Aydin, S; Boers, M; Cornell, C; Direskeneli, H; Gebhart, D; Hatemi, G; Luqmani, R; Matteson, E; Milman, N; Robson, J; Seo, P; et al. (Journal of Rheumatology, 2014)
The conduct of randomized controlled trials for vasculitis, especially for the antineutrophil cytoplasmic antibody-associated vasculitides [AAV, granulomatosis with polyangiitis (Wegener's) and microscopic polyangiitis], has been greatly advanced by the development, use, and acceptance of validated outcome measures. Trials have subsequently provided the opportunity to validate and refine reliable, valid outcome measures for these multisystemic and relapsing rare diseases. The Outcome Measures in Rheumatology (OMERACT) Vasculitis Working Group was formed in 2004 to foster development of validated and widely accepted outcomes in vasculitis using data-driven analyses, a dedication to building consensus, and adherence to, and guidance by, the principles of the OMERACT approach. This work led to the endorsement by OMERACT of the core set of domains and associated outcome measures for AAV. Next steps for the study of existing outcome tools in AAV include better definition of response criteria through development of more data-driven weighting of the elements of activity and damage assessment. The Working Group is now also embarking on a series of linked projects to develop validated patient-reported outcomes for use in clinical research in vasculitis. Additionally, the Working Group is studying how current methods of disease assessment and plans for new outcomes can be informed by the conceptual framework of the International Classification of Function of the World Health Organization. The success of the Group's work in AAV has also led to a formal process for developing outcomes for the large vessel vasculitides (Takayasu arteritis and giant cell arteritis) and Behçet disease.